2022
DOI: 10.3390/vetsci9100532
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility, Blood Parameters, Rumen Fermentation, Hematology, and Nitrogen Balance of Goats after Receiving Supplemental Coffee Cherry Pulp as a Source of Phytochemical Nutrients

Abstract: This research examines the impact of adding dried coffee cherry pulp (CoCP) to goat feed on the digestibility of the feed, rumen fermentation, hematological, and nitrogen balance. A goat feeding experiment employed four male crossbreds (Thai Native × Anglo Nubian) aged 12 months and weighing 21.0 ± 0.2 kg each. The treatment was conceived as a 4 × 4 Latin square with four specific CoCP levels at 0, 100, 200, and 300 g/day. Dry matter intake (DMI), organic matter intake (OMI), and crude protein intake (CPI) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
5
3
Order By: Relevance
“…The pH and temperature of the ruminal fluid obtained from this study were consistent with the findings of Maxiselly et al (2022), andSani et al (2023). The pH of the ruminal fluid is within the normal pH range of 5.5 to 7.0 reported to be optimal for microbial digestion of fibre and proteins in ruminants (Krause;Oetzel, 2006).…”
Section: Effect Of Cowpea Husk and Tiger Nut Residue In A Mixed Ratio...supporting
confidence: 92%
See 1 more Smart Citation
“…The pH and temperature of the ruminal fluid obtained from this study were consistent with the findings of Maxiselly et al (2022), andSani et al (2023). The pH of the ruminal fluid is within the normal pH range of 5.5 to 7.0 reported to be optimal for microbial digestion of fibre and proteins in ruminants (Krause;Oetzel, 2006).…”
Section: Effect Of Cowpea Husk and Tiger Nut Residue In A Mixed Ratio...supporting
confidence: 92%
“…The pH of the ruminal fluid is within the normal pH range of 5.5 to 7.0 reported to be optimal for microbial digestion of fibre and proteins in ruminants (Krause;Oetzel, 2006). The acetate to propionic acid ratio was lower than the range of 2.09 to 2.79 reported by Maxiselly et al (2022). The quantity of methane from this study was lower than the quantity (22.83-26.92 nm/L -1 ) reported by Maxiselly et al (2022).…”
Section: Effect Of Cowpea Husk and Tiger Nut Residue In A Mixed Ratio...contrasting
confidence: 42%
“…Blood metabolites are generally useful indicators of animal health and often reflect the metabolic homeostasis of the body. Levels of triglyceride and total cholesterol in the blood are commonly used to evaluate energy metabolism in dairy cows and small ruminants because they are closely linked to blood glucose concentration [ 40 ]. Blood cholesterol levels were significantly increased when ewes were injected with trace elements containing copper, manganese, and iodine [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The statistical analysis showed that the average consumption of DM, OM, and CP by the groups of ASE treatment at both concentrations (up to 5%), positive control, and negative control showed no significant difference between the pre-treatment and post-treatment (P>0.05). Maxselley et al [21] stated that the supplementation of 100-300 g/day of coffee cherry pulp containing phenolic compounds had no effect on the feed intake. Ardeshiri et al [22] added that the addition of Albizia lebbeck containing tannins had no effect on the consumption of DM, OM, and CP in Arabi sheep.…”
Section: Nutrient Intakesmentioning
confidence: 99%
“…In an in vivo study, Ibidhi and Salim [23] demonstrated that the administration of Trigonella foenum graecum L. seeds, which have high flavonoids, saponins, and phenolics, at concentrations of up to 30 g in the concentrate, did not affect the nutrient digestibility of the food in Barbarine sheep. However, every plant has different active compounds such as in the case study by Maxselley et al [21], which showed that the supplementation of CoCP at 300 g/day could have a negative impact on the digestion of feed possibly due to the presence of high phenolic compounds that affect the feed digestibility.…”
Section: Nutrient Digestibilitymentioning
confidence: 99%